2021
DOI: 10.3892/etm.2021.10840
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of circAtp9b in ulcerative colitis is induced by lipopolysaccharides and upregulates PTEN to promote the apoptosis of colonic epithelial cells

Abstract: It has been reported that knockdown of circular RNA (circ) ATPase class II type 9B (Atp9b) can reduce lipopolysaccharide (LPS)-induced inflammation, which plays a notable role in ulcerative colitis (UC). The present study aimed to explore the role of circAtp9b in UC. The expression levels of Atp9b and PTEN in the plasma of patients with UC (n=60) and healthy controls (n=60) were determined via reverse transcription-quantitative PCR. Overexpression of circAtp9b and PTEN were achieved in human colonic epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…27 In addition, circAtp9b, which was overexpressed in UC patients, had been shown to promote LPS-induced colonic epithelial cell apoptosis. 28 These results confirm the importance of circRNA in regulating UC process. Although previous studies have shown that circSOD2 may contribute to UC development by weakening the intestinal barrier, 13 more evidence is needed to further support the conclusion that circSOD2 is a potential target for treating UC.…”
Section: Discussionsupporting
confidence: 66%
“…27 In addition, circAtp9b, which was overexpressed in UC patients, had been shown to promote LPS-induced colonic epithelial cell apoptosis. 28 These results confirm the importance of circRNA in regulating UC process. Although previous studies have shown that circSOD2 may contribute to UC development by weakening the intestinal barrier, 13 more evidence is needed to further support the conclusion that circSOD2 is a potential target for treating UC.…”
Section: Discussionsupporting
confidence: 66%
“…Upregulated expression of circAtp9b was observed in plasma samples from UC patients ( 112 ). LPS treatment increased the expression of circAtp9b in human colonic epithelial cells, which increased the expression of PTEN, eventually promoting apoptosis in colonic epithelial cells.…”
Section: Roles Of Circrnas In Ibdmentioning
confidence: 99%
“…IL-3 is involved in UC through circular RNA circPan3 [ 10 ]. In ulcerative colitis, circRNA Atp9b is overexpressed [ 11 ]. CircRNA CCND1 is a new circRNA that has been shown to expedite cell metastasis and proliferation in hepatocellular carcinoma tumorigenesis by regulating the miR-497-5p/HMGA2 axis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%